The emerging role of autophagy in peroxisome dynamics and lipid metabolism of phyllosphere microorganisms - Oku, Masahide; Takano, Yoshitaka; Sakai, Yasuyoshi (Frontiers in Plant Science, 2014)
Eukaryotic microorganisms resident in the phyllosphere (above-ground, plant-surface environments) undergo dynamic changes in nutrient conditions and adapt their metabolic pathways during proliferation or in the course of infection of host plants. Some of these metabolic switches are accomplished by regulation of organelle abundance. Recent studies have shown that autophagy plays a major role in reducing the organelle quantity, thereby contributing to the metabolic switch required for survival or virulence of the microorganisms in the phyllosphere. In this minireview the metabolic pathways in several phytopathogenic fungi and the non-infectious asporogenous yeast Candida boidinii, which involve lipid droplets and peroxisomes, are summarized. The physiological functions of Atg (Autophagy-related) proteins in these organisms are discussed in relation to the dynamics of these two important organelles.